DEVELOPMENT OF SCIENTIFIC DISCIPLINES IN SUPPORTING PROFESSIONALISM AS EDUCATORS IN THE ERA 6.0 - Calysta, Nismara Putri; Sutama, I Wayan; Anisa, Nur (Proceeding of International Conference on Multidisciplinary Research, 2024)
Millennials or Generation Y are a group of people born after Generation X, namely people born in the range of 1980-2000. The image and concept of the teacher in contemporary society is very much different from that of the past. The past guru meant knowledgeable, wise, and wise. Currently, the teacher is seen as a function of education whose job is to teach based on certain scientific and academic qualifications. In general, teachers must understand the current social changes. Teachers should not stop learning about new things. Global challenges in the current era are also different from global challenges in the past. Whatever steps and methods are carried out in schools, of course, the aim is to shape character and prepare quality human resources. In this paper, the author will explain how to develop disciplinary knowledge related to multimedia and moral capabilities in supporting the professionalism of teaching staff as an effort to be made in facing challenges in the 6.0 era. Previously the author also explained about the 5.0 era, the millennial generation, and teacher professionalism.